Effects of order and sequence of resistance and endurance training on body fat in elementary school-aged girls - Alves, Ana R (2019)
The purpose of this study was to analyse the effects of order and sequence of concurrent resistance and endurance training on body fat percentage (BFP) in a large sample of elementary school-aged girls. One hundred and twenty-six healthy girls, aged 10-11 years (10.95 ± 0.48 years), were randomly assigned to six groups to perform different training protocols per week for 8 weeks: Resistance-only (R), Endurance-only (E), Concurrent Distinct Endurance-Resistance (CDER), Concurrent Parallel Endurance-Resistance (CPER), Concurrent Parallel Resistance-Endurance (CPRE), and a Control group (C). In R and E, the subjects performed single sessions of resistance or endurance exercises, respectively (two days per week). In CDER, resistance-endurance training was performed on different days each week (four days per week). CPER and CPRE performed single-session combined endurance-resistance training or combined resistance-endurance training, respectively, each week (two days per week). After an 8-week training period, BFP decreased in all experimental groups (CPER: 13.3%, p< 0.05; CPRE: 13.8%, p<0.001; E: 1.9%, p>0.05; R: 5.0%, p>0.05; and CDER: 5.6%, p>0.05). However, a significant difference was found in CPER and CPRE when compared to CDER, E, and R, indicating that training sequence may influence BFP. All programmes were effective, but CPER and CPRE obtained better results for BFP than CDER, E, or R. The effects of concurrent resistance and endurance training on body fat percentage can be mediated by order and sequence of exercise. These results provide insight into optimization of school-based fat loss exercise programmes in childhood.